The Effect of Service Quality, Cost, and Promotion on Parents' Decisions in Choosing Schools - Melvin Zakri (Peneliti.net, 2022)
This research aimed to understand the influence of Service Quality, Cost and Promotion on Parents Decisions in Choosing of School at Al Amanah Tangsel Vocational School in the field of Information and Communication Technology. The method in this research is the associative type with descriptive and quantitative approaches. Data that was used were Primary data and Secondary data. Primary data were collected through face-to-face interview, questionnaire and library research. Secondary data were collected through histories and documentations. The population and sample in this study amounted to 179 populations and used random sampling techniques with 124 respondents. The analysis tool uses multiple linear regression analysis with the help of SPSS 21 Software. The results showed that, Service Quality (X1), Cost (X2) and Promotion (X3) had a positive and significant effect partially and simultaneously. Service Quality (X1) contributed to Parents Decisions in Choosing (Y) of 68,4% and the remaining 31,6% was influenced by other factors. Hypothesis testing shows the value of tcount 16,236 > ttabel 1,979, and the value of sig < 0.05 at a = 5% then Ho1 is rejected and Ha1 is accepted. Cost (X2) contributed to Parents Decisions in Choosing (Y) of 53,7% and the remaining 46,3% was influenced by other factors. Hypothesis testing shows the value of tcount of 11,892 > ttabel 1,979, and the value of sig < 0.05 at a = 5% then Ho2 is rejected and Ha2 is accepted. The Promotion (X3) contributed to Parents Decisions in Choosing (Y) of 80,5% and the remaining 19,5% was influenced by other factors. The Hypothesis Test shows the value of t count 22,453 > ttabel 1,979, and the value of sig < 0.05 at a = 5% then Ho3 is rejected and Ha3 is accepted. Based on Coefficients test, the Unstandardized Coefficients B for Y = Y = 2.781 + 0.268X1 + 0.009X2 + 0.660X3. Based on R2 (determination coefficient) score, it is concluded that Service Quality (X1), Cost (X2) and Promotion (X3) contributed to Parents Decisions in Choosing (Y) by 84,2% and the remaining 15,8% was influenced by other factors. Simultaneous hypothesis test shows the value of Fcount 213,525 > Ftabel 2,68, and the value of sig < 0.05 at a = 5% then Ho4 is rejected and Ha4 is accepted. It shows that there are positive and significant impacts that simultaneously influence Service Quality, Cost and Promotion on Parents decisions in choosing of School at Al Amanah Tangsel Vocational School in the field of Information and Communication Technology